Effect of scutellarin on the metabolism and pharmacokinetics of clopidogrel in rats. (22nd October 2014) - Chen, Xinmeng; Jin, Jing; Chen, Yaobin; Peng, Lingling; Zhong, Guoping; Li, Jiali; Bi, Huichang; Cai, Yefeng; Huang, Min
Abstract Erigeron breviscapus (Vant.) Hand‐Mazz, a traditional Chinese medicine, is often co‐prescribed with clopidogrel for the treatment of ischemic vascular diseases. Scutellarin is the representative bioactive flavonoid isolated from this herb. The aim of this study was to explore the effect of scutellarin on the metabolism and pharmacokinetics of clopidogrel. The in vitro studies using rat liver microsomes showed that scutellarin significantly inhibited the metabolism of clopidogrel. The IC50 value was 2.1 µm. Ten male rats were employed to investigate the effect of scutellarin on the pharmacokinetics of clopidogrel in vivo. After pretreatment with scutellarin, there were significant increases in the AUC0–∞ (from 0.9 ± 0.4 to 1.7 ± 0.6 ng/ml h; p <0.05) and Cmax (from 0.4 ± 0.1 to 0.9 ± 0.1 ng/ml; p <0.05) of clopidogrel. The pharmacokinetic data for clopidogrel active metabolite showed significant decreases in AUC0–∞ (18.2 ± 5.6 to 11.4 ± 3.7 ng/ml h; p <0.05) and Cmax (from 8.2 ± 1.2 to 4.3 ± 0.3 ng/ml; p <0.05) after pretreatment with scutellarin. Collectively, the metabolism and pharmacokinetics of clopidogrel were significantly affected by scutellarin. This study indicated that potential herb–drug interaction between scutellarin and clopidogrel should be taken into consideration in clinical use. Copyright © 2014 John Wiley & Sons, Ltd.